BUKTI ELEKTRONIK SEBAGAI ALAT BUKTI YANG SAH DALAM HUKUM ACARA PIDANA - Ramiyanto Ramiyanto (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2017)
The Criminal Procedure Code as a general criminal procedure does not recognize electronic evidence as one of the admissible types of evidence. In practice, electronic evidence is also used as an admissible evidence to prove the criminal offenses in court. From the results of the discussion it can be concluded that electronic evidence in criminal procedure law is a dependent evidence and an independent evidence (substitution of letter proof if it meets the principle of functional equivalent approach and expansion of evidence) as specified in several special laws and instruments issued by the Supreme Court. The electronic evidence is not regulated in the Criminal Procedure Code as a lex generalis, however, to achieve material truth it can also be used as a valid evidence for the provision of all types of criminal offenses in court. It is based on recognition in the practice of criminal justice, some special laws, and instruments issued by the Supreme Court.Keywords: electronic evidence, admissible evidence, criminal procedure code, proof